Paper‐Based, Chemiresistive Sensor for Hydrogen Peroxide Detection. Issue 4 (24th February 2021) - Giaretta, Jacopo Emilio; Oveissi, Farshad; Dehghani, Fariba; Naficy, Sina
Abstract: Detecting hydrogen peroxide (H2 O2 ) as the side product of enzymatic reactions is of great interest in food and medical applications. Despite the advances in this field, the majority of reported H2 O2 sensors are bulky, expensive, limited to only one phase detection (either gas or liquid), and require multistep fabrications. This article aims to address some of these limitations by presenting a 3D printable paper‐based sensor made from poly(3, 4‐ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) decorated with horseradish peroxidase, an enzyme able to interact with H2 O2 . Unlike most electrochemical PEDOT:PSS‐based H2 O2 sensors with voltametric or potentiometric mechanisms, the sensing mechanism in this technology is impedimetric, significantly simplifying the fabrication process. Here, the resistance of sensors proportionally changes with H2 O2 concentration upon exposure to liquid or gas with a linear trend within the range of 61.3 × 10 −9 and 61.3 × 10 −6 m H2 O2 . The observed correlation between the resistance and H2 O2 concentration is highly dependent on the level of integrated enzyme, suggesting the direct contribution of horseradish peroxidase in the co‐redoxing of PEDOT:PSS in the presence of H2 O2 . Raman and UV–vis spectroscopies also confirm the structural change of PEDOT in the presence of H2 O2 which is facilitated by the enzyme. Abstract : Horseradish PEDOT‐PSS ink deposited on paper can detect hydrogen peroxide (H2 O2 ) in both liquid and vapor phase in concentration as low as 61.3 × 10 −9 m . The sensor shows two interactions zones depending on H2 O2 concentration. The mechanism of detection is based on the change in bipolaron concentration caused by the enzymatic redox reaction catalyzed by the enzyme.